The Beilstein System: Strategies for Effective Searching - James W. Oliver (Issues in Science and Technology Librarianship)
This article reviews the book The Beilstein System: Strategies for Effective Searching. Washington DC: American Chemical Society, 1998. 208 pages, edited by Stephen R. Heller.